2019
DOI: 10.1111/lam.13211
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic survival during a multi‐layered tablet development as tested in a dynamic, computer‐controlledin vitromodel of the stomach and small intestine (TIM‐1)

Abstract: The aim of the research was to develop a galenical formulation for the combination of the three probiotic strains Lactobacillus gasseri PA 16/8, Bifidobacterium longum SP 07/3 and Bifidobacterium bifidum MF 20/5 that would lead to the presence of a high amount of viable cells in the small intestine, the presumed site of action of these strains. This was tested in a validated, dynamic in vitro model of the stomach and small intestine (TIM‐1), simulating human adults after intake of a meal. Experiments were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The ability to directly observe the disintegration of the capsules within the gastric compartment was noted as a useful feature of the TIM-1 apparatus in this particular study [146]. TIM-1 has also been reported to have been used to optimize the composition of an enteric coating as well as the thickness that should be applied to a probiotic ingested tablet [147]. This study also permitted an alteration in the GI conditions to replicate an elderly as well as a healthy adult population to ensure that the results observed are relevant to the appropriate patient population [147].…”
Section: Tim-1 Gastric Compartmentmentioning
confidence: 94%
“…The ability to directly observe the disintegration of the capsules within the gastric compartment was noted as a useful feature of the TIM-1 apparatus in this particular study [146]. TIM-1 has also been reported to have been used to optimize the composition of an enteric coating as well as the thickness that should be applied to a probiotic ingested tablet [147]. This study also permitted an alteration in the GI conditions to replicate an elderly as well as a healthy adult population to ensure that the results observed are relevant to the appropriate patient population [147].…”
Section: Tim-1 Gastric Compartmentmentioning
confidence: 94%
“…Results showed a high survival rate of probiotic strain in the upper GI tract whereas the strain was more sensitive to colonic conditions. Venema et al [ 212 ] studied the survival of multilayer-coated probiotic strains ( L. gasseri PA 16/8, B. longum SP 07/3, and B. bifidum MF 20/5) using the TNO GI model (TIM-1 system)—the in vitro model of the stomach and small intestine. They have reported that the gastric survival percentage of Bifidobacteria and L. gasseri at 72% and 53%, respectively, were delivered to the small intestine.…”
Section: Methods To Confirm the Targeted Delivery And Viability Of Encapsulated Probioticsmentioning
confidence: 99%
“…different ages or healthy or pathological situations (Sniffen et al, 2018). Ideally, probiotic strains should exhibit a natural tolerance to gastric and bile acids, as well as sufficient resistance against digestive enzymes which favours their survival during the passage through stomach and upper intestinal tract (Venema et al, 2019). As it is frequently not the case, diverse strategies that protect probiotics against gastric acidity can be applied, such as microencapsulation (Surono et al, 2018) and enteric coating of tablets (Eiberger et al, 2011).…”
Section: Impact Of Oral Galenic Formulations Ofmentioning
confidence: 99%
“…Among available models, the well-validated dynamic systems, such as the TNO gastrointestinal model (TIM-1), the Simulator of the Human Microbial Ecosystem (SHIME) and the Artificial colon (ARCOL) are those that are more closely reproducing in vivo conditions. They have been successfully used for probiotic testing (Blanquet-Diot et al, 2012;Cordonnier et al, 2015;Patrignani et al, 2019;Thévenot et al, 2015;Van den Abbeele et al, 2012;Venema et al, 2020Venema et al, , 2019. In the present study, we used two complementary dynamic in vitro models, TIM-1 which simulates the human stomach and three parts of the small intestine and ARCOL which reproduces the human colon, to assess the impact of three galenic formulations (powder, capsule and sustained-release tablet) of a L. salivarius strain on its survival all along the gut and interactions with resident gut microbiota.…”
Section: Impact Of Oral Galenic Formulations Ofmentioning
confidence: 99%